STASIUN INTERCHANGE MRT BLOK M DENGAN PENDEKATAN ARSITEKTUR BIOKLIMATIK DI JAKARTA - Naya Marsatyasti; Agung Kumoro; Agus Heru Purnomo (Universitas Sebelas Maret Surakarta, 2015)
Everyday, more than four million commuters from DKI Jakarta’s satellite regions commute to and from capital region. The tendency of Jabodetabek’s expansion is so high that rising transportation cost significantly, decreasing level of mobility and quality of life. As shown in DKI Jakarta’s SLHD (Status Lingkungan Hidup Daerah) in 2012, in order to support DKI Jakarta’s transportation issues and decreasing impact of air pollution in Jakarta as a result of vehicles’s usage, MRT is proclaimed to be one of transportation’s solution. Aside from how to plan and design good MRT station both in terms of passengers needs of mobility, thermal requirement is also a design problem for building; associated with Jakarta located in tropical climate zone. Method or approach used is based on Bioclimatic Architecture focused on building thermal requirements obtained through bioclimatic chart analysis with manifestations of building mass arrangement to best orientation, percentage of openings and shadings to maximize natural lighting and ventilation, building material, landscape composition and building arrangement. The results obtained is Blok M MRT station design used as mass transportation systems’s facilities based on Bioclimatic Architecture’s principle. Keywords: Architecture, Bioclimatic, Blok M, Mass Rapid Transit, Shading, Station.